Environmental performance of kitchens – A case study of a Ballingslöv kitchen from a life cycle perspective - Johansson,Annie (2020)
Kitchens are an essential part of the interior design in buildings. With the increased focus on sustainability in the building industry it is therefore of interest to investigate the environmental performance of kitchens. By using life cycle assessment (LCA) as a tool three different tabletops (composite, solid wood and laminate), a door, a frame as well as the entire standard kitchen are investigated. A literature study on customer behaviour, trends and drivers on the market is combined with the results from the LCA studies to investigate how the results can be useful in affecting the behaviour of customers. The results from the LCA studies show that the composite tabletop has a significantly higher impact than the solid wood and laminate tabletop. The trend for the tabletops is that the raw material phase contributes most to the total impact. The same trend is seen for the door and frame. For the standard kitchen the most impacting components are the white goods, the electricity in the user phase and the composite tabletop. To improve the environmental performance of a standard kitchen, the white goods should be of high quality with a long lifetime and require little electricity in the user phase. A solid wood or laminate tabletop should be chosen over a composite tabletop. Using electricity from renewable sources in the production in the supply chain as well as using sustainable transports are other means of improving the environmental performance. The literature study shows that there is a lack of studies that specifically address customer behaviour in connection to the kitchen market. There is also a lack of information on environmental performance of kitchens in general. Some general trends, drivers and customer behaviours could be identified in a broader perspective. There is an increased interest for sustainability issues among customers and a higher demand for transparent and honest information as well as communication on this subject. There is a connection between honest sustainability communication and the credibility of the company or brand as well as the motivation to buy environmentally adapted products, even at a higher cost. To adhere to the requests from customers on more specific information about the environmental impact of products LCA can be useful. It generates possibilities to advice the customer on which components they should choose to improve the environmental performance of their kitchen. The customer behaviour can also be affected by informing the customer of the importance to keep their kitchen longer or encourage the customer to second-hand trade when changing kitchen (or parts of it).
Keywords: Kitchen; Life cycle assessment; Consumer behaviour; Tabletop